Financial management : - Brooks, Raymond (Pearson Education, 2016)
Financial Management: Core Concepts. The ideal resource for non-finance majors presents the key elements of financial operations. The book and support materials are student-centered, as readers build their skills and test their knowledge by forging connections between ideas and applying them to real-world situations. With the latest financial information available, the 4th Edition makes finance interesting and accessible to students unfamiliar with this topic by relating it to their own personal experiences and exploring this field across all disciplines.